Understanding Addition inference Rule

discrete mathematicslogicnatural-deduction

Studying Discrete Structures, Logic, And Computability by James L. Hein, came across this proof.

On line 3, the author uses that rule to get $A v B$. Two questions arose:

  1. Is it possible to introduce a variable that was not mentioned in the Premises ? What would be the reasoning behind that ?
  2. Is it possible to introduce a variable that was mentioned in the Premises with the opposite truth value (negated if it wasn't or vice versa) ?

Example 6

Best Answer

  1. Is it possible to introduce a variable that was not mentioned in the Premises ? What would be the reasoning behind that ?

Yes.   If $A$ holds in the context, then you may infer that $A\vee B$ holds (whether $B$ does or does not).   After all, $A\vee B$ is the claim that at least one from $A$ or $B$ holds.   So when at least one does (eg $A$), then the disjunction holds too.

PS: the rule of Addition is not about adding the whole statement.   In logic proof systems, it refers to the rule by which any disjunct can be added to an existing statement.   That if $A$ is derivable (or assumed), then $A\vee B$ may be inferred in the same context.

  1. Is it possible to introduce a variable that was mentioned in the Premises with the opposite truth value (negated if it wasn't or vice versa) ?

It is possible to raise an assumption (rule P) that contradicts a prior statement.   You may open a sub-proof by assuming anything as needed for the sake of argument; just be sure to close the sub-proof by discharging it with a valid rule (such as rule CP, "conditional proof").

This is the Principle of Explosion, otherwise known as ex falso (sequitur) quodlibet (Latin for "from falsehood, anything follows").   If your premises contain a contradiction, you can derive anything via valid rules of derivation.   Since it is valid to do so, therefore you may do so.


So you want to prove $\neg A\to(A\to B)$? Well, since that is a conditional statement, you should use a conditional proof: raise $\neg A$ as an assumption with the aim to derive $A\to B$.

So you want to prove $A\to B$, under the assumption of $\neg A$? Well, again you should use a conditional proof: raise $A$ as an assumption with the aim to derive $B$.

So you want to prove $B$ under the assumptions of $\neg A$ and $A$? Well, you have assumed $A$ so you may infer $A\vee B$ (via Addition), but you have also assumed $\neg A$, so you may further infer $B$ (via Disjunctive Syllogism).

Why now, you have successfully derived $B$ in the context of the two assumptions, $\neg A$ and $A$, so you may now discharge those assumptions to close the two conditional proofs.

Thus you have proven $\neg A\to(A\to B)$ using the rules of assumption, conditional proof, addition, and disjunctive syllogism.